PENGARUH PERSONAL SELLING DAN DIRECT MARKETING TERHADAP PENINGKATAN VOLUME PENJUALAN MOTOR BEAT PADA PT. HONDA INDAKO BINJAI - Halawa, Nuraida Hasna; Saragih, Nawary (LPPM Universitas Katolik Santo Thomas Medan, 2024)
The aim of the research is to determine the influence of personal selling and direct marketing on increasing the sales volume of Beat motorbikes at PT. Honda Indako Binjai. Data collection was carried out by distributing questionnaires to 92 consumers who purchased Honda Beat motorbikes at PT. Honda Indako Binjai. The testing technique used is multiple linear regression analysis, hypothesis testing, F test and t test. Data processing using SPSS version 25. The research results show that simultaneously personal selling and direct marketing have a positive and significant effect on increasing sales volume with 5 percent. Partially, it shows that personal selling and direct marketing have a positive and significant effect on increasing sales volume with 5 percent. The coefficient of determination (R Square) value is 0.676, meaning that the increase in sales volume can be explained by personal selling and direct marketing by 67.6%, while another 32.4% is explained by other factors not explained in this research.